Bryophyte flora of Greater Mymensingh District of Bangladesh - Class : Bryopsida - Banu-Fattah, Khurshida; Sarker, Sujan Kumer (Bangladesh Journal of Plant Taxonomy, 2007)
The Greater Mymensingh District, particularly the hilly areas are rich in bryophyte flora. The present paper on Bryopsida is based upon primary as well as secondary data collection and includes an account of 51 species under 35 genera, 21 families and nine orders. A short description of each species with locations, dates of collections and name of collectors are provided. Key words: Bryophytes, Bryopsida, Mosses, Mymensingh District, Bangladesh DOI: 10.3329/bjpt.v14i1.522 Bangladesh J. Plant Taxon. 14(1): 47-66, 2007 (June)